Analysis of the Policy on Implementing Digital Population Identity in the Compulsory E-KTP Community in Surakarta City - Abrianto, Diar Dwi; Fathurahman, Heri (Universitas Teuku Umar, 2024)
This research focuses on evaluating the policy implementation of Digital Population Identity in Surakarta City, particularly for citizens required to have an E-ID card (KTP-el). Through a series of population organization and regularization efforts, the primary objective of the study is to ensure the fulfillment of population rights and provide legal certainty regarding the legality of population documents. The research employs a qualitative method with a constructivist paradigm and a single instrumental case study approach, conducted at the Surakarta City Population and Civil Registration Office. The study gathers both primary and secondary data relevant to the topic. Descriptive analysis is employed to present an overview of the policy on the implementation of Digital Population Identity in Surakarta City, particularly for citizens obligated to have an E-ID card. The research findings conclude that the policy implemented by the Surakarta City Population and Civil Registration Office regarding the application of Digital Population Identity for citizens with mandatory E-ID cards can be considered successful, particularly in terms of coverage using the applied method. Therefore, this research not only provides a comprehensive overview of the policy but also demonstrates its effectiveness and significant benefits in terms of coverage. This evaluation can serve as a foundation for further improvements or as a reference for other regions planning to implement similar policies in managing digital population identities.